2009
DOI: 10.1088/0953-8984/21/20/204107
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of confined suspensions of swimming particles

Abstract: Low Reynolds number direct simulations of large populations of hydrodynamically interacting swimming particles confined between planar walls are performed. The results of simulations are compared with a theory that describes dilute suspensions of swimmers. The theory yields scalings with concentration for diffusivities and velocity fluctuations as well as a prediction of the fluid velocity spatial autocorrelation function. Even for uncorrelated swimmers, the theory predicts anticorrelations between nearby flui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 29 publications
10
103
2
Order By: Relevance
“…In their seminal work, Wu and Libchaber 25 experimentally found that D eff increased linearly with c in suspensions of E. coli. Subsequent studies 26,27,[29][30][31][32] have observed that this scaling holds at low concentrations and in the absence of collective motion. In this regime, D eff can be decomposed into additive components as 26,27,[29][30][31][32] where D 0 and D A are the thermal and active diffusivities, respectively.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In their seminal work, Wu and Libchaber 25 experimentally found that D eff increased linearly with c in suspensions of E. coli. Subsequent studies 26,27,[29][30][31][32] have observed that this scaling holds at low concentrations and in the absence of collective motion. In this regime, D eff can be decomposed into additive components as 26,27,[29][30][31][32] where D 0 and D A are the thermal and active diffusivities, respectively.…”
Section: Introductionmentioning
confidence: 91%
“…Subsequent studies 26,27,[29][30][31][32] have observed that this scaling holds at low concentrations and in the absence of collective motion. In this regime, D eff can be decomposed into additive components as 26,27,[29][30][31][32] where D 0 and D A are the thermal and active diffusivities, respectively. It has been proposed that the active diffusivity D A is a consequence of advection due to far-field interactions with bacteria 26 and may even be higher near walls 26,27 .…”
Section: Introductionmentioning
confidence: 91%
“…This approach yields some interesting preditions on long-ranged hydrodynamical coupling between different swimmers as well as between cells and surfaces (see e.g. [158,205,7,272,159,276], or a recent review in [206]). However, recent a recent experiments with E. Coli conducted by Drescher et al [86], show that in most cases the effects of long-ranged hydrodynamic interactions are negligible in comparison to the intrinsic stochasticity in the motion of bacteria (i.e.…”
Section: Individual Dynamics -Experiments and Modelsmentioning
confidence: 99%
“…[19][20][21][22] Alternatively, a number of studies have focused on the collective behavior of bacteria swarm, both experimentally [23][24][25][26][27] and theoretically. 23,[28][29][30][31][32] Investigations have shown that bacterial suspensions develop transient patterns of coherent locomotion with correlation lengths much larger than the size of individual organisms. 23,26,28 Such collective motion has been used, for example, to induce mixing in microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%